RESEARCH OF HOURGLASS MODE’S CONTROL IN THE SIMULATION OF THE SQUEEZING OF OCEAN CABLE - LI Jing; WANG GuiLu; WEI Yong (Jixie qiangdu)
The hourglass mode emerging from the analysis of the lateral pressure for the submarine cable,which makes effect of the accuracy of the simulation results. Different hourglass control modes were adopted to find out the reasons for the formation of the hourglass. and emphasis on distinguishing the parts which have serious hourglass mode and the control method were introduced. Firstly this paper finds out which components have the serious hourglass mode. Then several control methods of the hourglass mode were studied and compared by adjusting the different hourglass control coefficient,the most effective control method was concluded and a more accurate result was got.